Educational Psychology-Empowered Creative Practice Strategy and Educational Countermeasures for Cinematography Major - Di, Hanwei (Frontiers in Psychology, 2022)
This work aims to improve Cinematography Majors' creative orientation and practical skills and improve related teaching quality. Firstly, this work analyzes the theoretical knowledge and main working principles of Educational Psychology (EPSY). Then, it reviews the current situation and characteristics of the Cinematography teaching through a Questionnaire Survey (QS). Consequently, an EPSY-based teaching effect evaluation model is proposed for Cinematography Majors. The results show that genders have great differences in Cinematography Majors' theoretical knowledge and creative orientation. Girls' theoretical knowledge learning effect is better than boys, with about 84% qualification rate at best. Boys' creative orientation learning effect is better than girls, with the highest qualification rate of about 84%. Meanwhile, students' theoretical knowledge differs greatly from grade to grade and the learning effect increase with the grade. Nevertheless, students' overall creative orientation is not satisfactory. Lastly, students' theoretical knowledge differs greatly given different artistic backgrounds, but the difference in creative orientations is small. Thus, the school can carry out targeted teaching for students according to different genders, grades, and artistic backgrounds, to comprehensively improve the teaching effect of Cinematography. The finding provides technical support and educational countermeasures for improving the teaching effect of Cinematography and the reform of Cinematography teaching.